2023
DOI: 10.1001/jamanetworkopen.2022.49560
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Psychiatric Disorders Among Spouses of Patients With Cancer in Denmark and Sweden

Abstract: ImportanceThere is emerging evidence that spouses of patients with cancer may have a higher prevalence of mental illness, but these studies have been limited by pre-post designs, focus on a single mental illness, and short follow-up periods.ObjectivesTo assess the overall burden of psychiatric disorders among spouses of patients with cancer vs spouses of individuals without cancer and to describe possible changes in this burden over time.Design, Setting, and ParticipantsThis population based cohort study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(94 reference statements)
0
8
0
Order By: Relevance
“… Hu et al (2023) showed a higher risk of any mental disorder in spouses of cancer patients compared to spouses of individuals without cancer in a binational study in Denmark and Sweden. The risk of first-onset mental disorders increased by 30% during the first year after cancer diagnosis, especially for depression and stress-related disorders.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“… Hu et al (2023) showed a higher risk of any mental disorder in spouses of cancer patients compared to spouses of individuals without cancer in a binational study in Denmark and Sweden. The risk of first-onset mental disorders increased by 30% during the first year after cancer diagnosis, especially for depression and stress-related disorders.…”
Section: Introductionmentioning
confidence: 97%
“…Many informal caregivers also face a difficult task: while they are often the main source of emotional and practical support for the sick person and are involved in medical decision-making (Ernst et al, 2017;Laidsaar-Powell et al, 2017;Weissflog et al, 2017;Cincidda et al, 2022), they themselves have a high psychosocial burden that requires support (Zimmermann, 2022). Hu et al (2023) showed a higher risk of any mental disorder in spouses of cancer patients compared to spouses of individuals without cancer in a binational study in Denmark and Sweden. The risk of first-onset mental disorders increased by 30% during the first year after cancer diagnosis, especially for depression and stress-related disorders.…”
mentioning
confidence: 97%
“…A. Given et al, 2004;Hsu et al, 2014;Hu et al, 2023;Northouse et al, 2012). Ample evidence also suggests that cancer caregiving can introduce problems or magnify preexisting tensions in the wider family network (Girardon-Perlini & Ângelo, 2017;Nissen et al, 2016;A.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given the high risk of psychopathological disorders in the relatives of patients with cancer, such new cost-effective interventions should also be available to them. 9 In the last two decades, digital technologies have expanded tremendously. Technologies developed to support human health and well-being are more recent, and their effectiveness and impact on the healthcare system need to be evaluated constantly.…”
Section: Introductionmentioning
confidence: 99%
“…These costs can be related, for example, to the professional who takes more time with one patient to the detriment of others, additional training costs, or increased demand. In addition, given the high risk of psychopathological disorders in the relatives of patients with cancer, such new cost‐effective interventions should also be available to them 9 …”
Section: Introductionmentioning
confidence: 99%